1998
DOI: 10.1083/jcb.143.4.1041
|View full text |Cite
|
Sign up to set email alerts
|

When Overexpressed, a Novel Centrosomal Protein, RanBPM, Causes Ectopic Microtubule Nucleation Similar to γ-Tubulin

Abstract: A novel human protein with a molecular mass of 55 kD, designated RanBPM, was isolated with the two-hybrid method using Ran as a bait. Mouse and hamster RanBPM possessed a polypeptide identical to the human one. Furthermore, Saccharomyces cerevisiae was found to have a gene, YGL227w, the COOH-terminal half of which is 30% identical to RanBPM. Anti-RanBPM antibodies revealed that RanBPM was localized within the centrosome throughout the cell cycle. Overexpression of RanBPM produced multiple spots which were colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
152
1
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(159 citation statements)
references
References 92 publications
4
152
1
2
Order By: Relevance
“…RanBPM is a scaffold protein known to interact with different receptors including c-Met and to facilitate their activation (35), but it has also been reported to be incapable of interacting with the EGFR (36). In addition, although RanBPM was originally identified in a yeast two-hybrid screen using Ran as bait (37), thus far there is little evidence in the literature to support the idea that RanBPM is a bona fide Ran target, and we have not been able to detect an interaction between Ran and RanBPM in our stable cell lines (data not shown).…”
Section: Discussionmentioning
confidence: 38%
“…RanBPM is a scaffold protein known to interact with different receptors including c-Met and to facilitate their activation (35), but it has also been reported to be incapable of interacting with the EGFR (36). In addition, although RanBPM was originally identified in a yeast two-hybrid screen using Ran as bait (37), thus far there is little evidence in the literature to support the idea that RanBPM is a bona fide Ran target, and we have not been able to detect an interaction between Ran and RanBPM in our stable cell lines (data not shown).…”
Section: Discussionmentioning
confidence: 38%
“…Although most of the Ran-binding proteins play an important role in nucleocytoplasmic transport, it is unlikely that RanBPM is involved in this process (Nishitani et al, 2001). Alternatively, Nakamura et al (1998) reported that RanBPM might be involved in reorganization of the microtubule network; however, the precise function of RanBPM remains unknown.…”
mentioning
confidence: 99%
“…Given that RanBPM is localized in both the cytoplasm and nucleus (Nakamura et al, 1998;Nishitani et al, 2001), it is probable that p73a might have an ability to promote nuclear translocation of RanBPM through the physical interaction between them. As described previously, wildtype p53 is predominantly localized in the cytoplasm of many neuroblastoma cells (Moll et al, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ran-BPM/RanBP9 was originally cloned as a Ran-binding protein and found to be localized in both the nucleus and cytoplasm (32,33). RanBPM contains a very conserved SPRY domain with unknown functions.…”
mentioning
confidence: 99%